2018
DOI: 10.1097/opx.0000000000001232
|View full text |Cite
|
Sign up to set email alerts
|

Using an Augmented Reality Device as a Distance-based Vision Aid—Promise and Limitations

Abstract: SIGNIFICANCEFor people with limited vision, wearable displays hold the potential to digitally enhance visual function. As these display technologies advance, it is important to understand their promise and limitations as vision aids.PURPOSEThe aim of this study was to test the potential of a consumer augmented reality (AR) device for improving the functional vision of people with near-complete vision loss.METHODSAn AR application that translates spatial information into high-contrast visual patterns was develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 28 publications
2
43
0
Order By: Relevance
“…Only 10 of the studies reviewed involved a quantitative assessment of mobility performance and of these, 8 of them [45][46][47][48][52][53][54]77 recorded a significant reduction in efficiency with vision enhancement. Of the other two studies, which observed similar or better efficiency, in both of them, 68,76 the mobility courses were relatively simple with large walkable areas and a small number of relatively large obstacles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 10 of the studies reviewed involved a quantitative assessment of mobility performance and of these, 8 of them [45][46][47][48][52][53][54]77 recorded a significant reduction in efficiency with vision enhancement. Of the other two studies, which observed similar or better efficiency, in both of them, 68,76 the mobility courses were relatively simple with large walkable areas and a small number of relatively large obstacles.…”
Section: Discussionmentioning
confidence: 99%
“…OSTs 45,60 are the most commonly used type of displays in AR environments as they allow users to see the real-world enhanced with virtual objects or holograms (e.g. Magic Leap, Microsoft HoloLens, Google Glass, and Epson Moverio BT-300).…”
Section: Optical See-through Displaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research indicates that there are a number of barriers that prevent the current technologies to provide each individual patient with specialized assistance in enhancing the remaining vision, [13]. For example, there is a need to systematically examine how acuity level and visual field loss is associated with specific eye conditions, and how to utilize this connection to deliver specialized visual aid.…”
Section: Motivationsmentioning
confidence: 99%
“…With the recent boom of technological advancements in cameras and headwear, many companies have been approaching the problem by combining augmented reality with headworn devices such as Glass (Google, Mountain View, CA) and HoloLens (Microsoft, Redmond, WA). [13][14][15][16][17] Aira (available in the public domain at https://aira.io/; Aira Tech Corporation, La Jolla, CA) uses on-demand augmented reality assistive wearable technology designed for the SVI but relies on human-human intelligence instead of computed artificial intelligence or unidirectional output as its method of assistance. The user wears glasses with a video camera mounted that, when activated, livestreams to an "agent" who assists the user in the specified task.…”
Section: Introductionmentioning
confidence: 99%